Lead sorption and leaching from an Inceptisol sample amended with sugarcane vinasse (Scientia Agricola, 2010)
Vinasse is produced at high amounts by the ethanol and sugarcane spirits industries. Although the effects of vinasse on soil attributes are well elucidated, little is known about its effects on sorption and leaching of lead (Pb) from soils. This work evaluated the Pb sorption and leaching from disturbed topsoil samples (0-20 cm) of an Inceptisol, under the influence of sugarcane vinasse. Pb sorption was evaluated by batch sorption method, using air-dried samples (< 2 mm) treated with pure (100%), and diluted (20%, and 50%) vinasse. The amended soil samples were further reacted with 0.05; 0.10; 0.25; 0.50, and 0.75 mmol L-1 of Pb. To measure the Pb leached, soil columns were packed in PVC tubes, 12-cm long with 4-cm internal diameter filled with 200 g of treated soil. The vinasse doses applied over the columns corresponded to 0 (control), 150 and 300 m³ ha-1. Seven days later, 5 mL of a Pb solution (100 mmol L-1) was applied on the columns; they were successively leached and Pb was measured in the leachates. The vinasse increased the maximum sorption capacity and binding energy of Pb with the soil when at equilibrium conditions. However, at non-equilibrium conditions, the vinasse enhanced the Pb leaching. From these results, it is advised that special attention must be given to Pb contaminated areas where vinasse is applied.